Effectiveness of the fishbone strategy on cognitive achievement and attitudes in physical education teaching methods - Azez, Ahlam Dara; Salman, Rabih Hazem; Ahmed, Enas Enad (Tanjungpura Journal of Coaching Research, 2026)
Background The educational system is based on preparing an educated generation capable of shouldering the burden of developing scientific disciplines, thereby building society on solid foundations. This requires rapid development across all areas of life and the search for means, methods, and strategies that advance the learning process. Objectives This research aims to identify the impact of the fishbone strategy on the achievement of 3rd-grade students in teaching methods and on their attitudes toward it. Methods The research sample comprised 30 third-year students in the Faculty of Physical Education and Sports Sciences at Mosul University during the second semester of the academic year (2024-2025). The researchers used the experimental design and prepared the experimental group’s curriculum and the control group. The statistical means were used to process the data. Results They found that the students in the experimental group outperformed those in the control group on the achievement test and the trend scale. Also, results show that there is a statistically significant difference in the parts of the achievement test as well as the total score of the test in the subject between the two research groups. Conclusion Using the fishbone strategy with its stages and activities contributed to the improvement of the students of the experimental group over their peers from the control group in achievement. This is evidence that teaching using the fishbone strategy is more likely to foster cognitive achievement in the usual way. The researchers recommended diversifying the use of different and modern teaching methods and identifying the current strategic methods that have proven effective in increasing achievement and trends.